Establishing a Standardized Measure of Quality in Pediatric Liver Surgery: Definition and Validation of Textbook Outcome With Associated Predictors - Fuchs, Juri; Hoffmann, Katrin; Murtha-Lemekhova, Anastasia; Kessler, Markus; Günther, Patrick; Frongia, Giovanni; Probst, Pascal; Mehrabi, Arianeb (Frontiers in Surgery, 2021)
Purpose: To establish comparable reporting of surgical results in pediatric liver surgery, the recently introduced composite outcome measures Textbook Outcome (TO) and Comprehensive Complication Index (CCI) are applied and validated in a pediatric surgery context for the first time. In a representative cohort of pediatric patients undergoing liver resection, predictive factors for TO and CCI are investigated and outcomes compared to available literature on surgical outcomes of pediatric liver resection. Methods: All liver resections for patients under 21 years of age performed at the Department of General, Visceral, Transplantation and Pediatric Surgery of the University of Heidelberg between 2009 and 2020 were included in the analysis. Criteria for TO were defined prior to the analysis. Univariate and Multivariate regression was applied to identify factors associated with TO and CCI. Results: 53 pediatric patients underwent liver resections during the observation period. No 30- or 90-day mortality occurred. 23 patients (43.4%) had a TO. CCI and TO showed highly significant correlation (b = -30.33, 95% CI [-37.44; -23.22], p < 0.001). Multivariate analyses revealed significant association between intraoperative blood loss (adjusted for circulating blood volume) and CCI (b = 0.70, 95%CI [0.22; 1.32], p = 0.008) and failure to achieve TO (OR = 0.85, 95%CI [0.69; 0.97], p = 0.048). Conclusion: TO and CCI are suited outcome measures in pediatric surgical studies and offer objective comparability of results. Their application in clinical studies will be a major step forward to establish evidence-based therapies in pediatric surgery. Systematic utilization of TO and CCI can aid in generating comparable studies on surgical techniques and outcomes in pediatric liver resection.